2021
DOI: 10.1002/rth2.12513
|View full text |Cite
|
Sign up to set email alerts
|

Elevated von Willebrand factor levels during heavy menstrual bleeding episodes limit the diagnostic utility for von Willebrand disease

Abstract: Background Heavy menstrual bleeding (HMB) is often the first bleeding symptom for female individuals with inherited bleeding disorders. Guidelines recommend performing the hemostatic evaluation at HMB presentation. Von Willebrand factor (VWF) levels increase with stress, making it unclear if VWF studies during acute bleeding are beneficial in diagnosing von Willebrand disease (VWD). Objectives To determine the utility of testing for VWD during acute HMB. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…As mentioned above, both one‐stage and chromogenic FVIII levels should be measured when Haemophilia A is suspected. Testing for a coagulopathy in the setting of HMB can be complicated by elevations of VWF in the setting of HMB, as well as delayed platelet aggregation in the setting of anaemia (haemoglobin <10 g/dl) 38,39 . As such, repeat testing may be needed outside of the acute setting.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, both one‐stage and chromogenic FVIII levels should be measured when Haemophilia A is suspected. Testing for a coagulopathy in the setting of HMB can be complicated by elevations of VWF in the setting of HMB, as well as delayed platelet aggregation in the setting of anaemia (haemoglobin <10 g/dl) 38,39 . As such, repeat testing may be needed outside of the acute setting.…”
Section: Introductionmentioning
confidence: 99%
“…While plasma VWF:Ag or VWF:RCo >100 IU/dL has a neg a tive pre dic tive value >95% for VWD, 19 some patients ulti mately diag nosed with VWD may have ini tial test results within the nor mal range (>50 IU/dL). 19,20 In ado les cents with acute HMB, if plasma FVIII:C was not ele vated, only a min i mal change in VWF:Ag and VWF:RCo lev els was observed at retesting (2% and 1%, respec tively), suggesting FVIII:C lev els may help deter mine the need to retest. 20 In a small study of 22 irondefi cient women, retest ing fol low ing iron sup ple men ta tion iden ti fied type 1 VWD in 27% despite nor mal plasma VWF lev els on ini tial test ing.…”
Section: Should You Repeat a Bor Der Line Plasma Vwf Result?mentioning
confidence: 99%
“…19,20 In ado les cents with acute HMB, if plasma FVIII:C was not ele vated, only a min i mal change in VWF:Ag and VWF:RCo lev els was observed at retesting (2% and 1%, respec tively), suggesting FVIII:C lev els may help deter mine the need to retest. 20 In a small study of 22 irondefi cient women, retest ing fol low ing iron sup ple men ta tion iden ti fied type 1 VWD in 27% despite nor mal plasma VWF lev els on ini tial test ing. 21 Due to the known fluc tu a tions in plasma VWF, diag no sis in peo ple with bor der line plasma VWF lev els is more chal leng ing, often resulting in repeated plasma VWF test ing.…”
Section: Should You Repeat a Bor Der Line Plasma Vwf Result?mentioning
confidence: 99%
“…Emerging data suggest that iron deficiency may obscure a diagnosis of VWD due to elevations in VWF. 24 Brown and colleagues recently published a retrospective cohort study evaluating VWF antigen levels during acute bleeding and then repeating testing with resolution of bleeding, which demonstrated that factor VIII and VWF are elevated due to HMB. In total, 70% of patients diagnosed with VWD met diagnostic criteria with their inpatient laboratories and VWF levels >100% had high negative predictive value.…”
Section: Discussionmentioning
confidence: 99%